THE DEVELOPMENT OF INDEPENDENT LIVING SKILLS IN YOUNG ADULTS WITH INTELLECTUAL DISABILITY IN SHELTERED HOUSING ACCOMMODATION - Raudeliunaite, Rita; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
National Programme for Social Integration of People with Disabilities for 2013 - 2019 has set a strategic objective to create a positive environment and conditions for a dignified and fully fledged life of people with disabilities in Lithuania, to guarantee equal opportunities and the quality of life of people with disabilities. The article analyses the experiences of the social workers, who work in sheltered housing accommodation with young adults with intellectual disability, when developing independent living skills in young adults with intellectual disability. Sheltered housing accommodation is social services institutions providing social care, in which persons live in home environment and conditions are created for them to manage their own personal life on their own with the support of the social workers. A qualitative-empirical study has been conducted by using the method of a semi-structured interview. The study data were processed by using the method of content analysis. The results of the empirical study are based on the experience of 11 social workers, who have been working in sheltered housing accommodation with young adults with intellectual disability for at least 3 years. The study has revealed that the following independent living skills are considered to be the most easy to be developed: cooking, simple housework, hygiene skills. The young adults also easily develop public transport use skills. The young adults most often acquire work skills by tidying their home environment. The most difficult, according to the social workers, to develop are economic skills: to manage their budget, to allocate finances, to pay for services, and to do the shopping.  The young adults with intellectual disability find it difficult to develop their parenting skills.  Communication skills are developed while learning etiquette and complying with it in a large range of environments, by encouraging to  communicate courteously with other persons, showing personal example, taking a good example from others, taking part in different events, festivals and communal activity.  The development of independent living skills occurs by engaging young adults in a practical activity. Particular attention is given to the development of healthy lifestyle skills. The young adults are encouraged to make decisions by guiding them in the right direction, while respecting their interests; the responsibility for the decisions made by them and the consequences of those decisions is also developed. Activity planning, organising and personal skills are developed.